Marketing Communication Strategy of PT. Cyber Edu Inkor in Promoting Cyber Learning Programs - Djudjur Luciana Radjagukguk; Hajid Arrafi (IJESS International Journal of Education and Social Science, 2022)
The technology market is getting more advanced from time to time, especially in the world of education, which is known as cyber education or Cyber ​​Learning. One of them is PT. Cyber ​​Edu Inkor is a service or product company that runs cyber education programs for the advancement of education, because there are still people in Indonesia who have not received education evenly. The presence of PT. Cyber ​​Edu Inkor himself explained that there are many ways to make digital-based learning so that it can be accessed by the wider community, using one of the technologies. The purpose of this study to analyze PT. Cyber ​​Edu Inkor promotes the cyber learning program through various stages in implementing marketing communication strategies through the implementation of the 7P Promotional Mix including: product, price, place, promotion, people, physical evidence, and process. Besides that, PT. Cyber ​​Edu Inkor implements a strategy through the stages of Business to Business (B2B) marketing by selling its products/services from one company to another. The method used is a qualitative research method, namely conducting virtual interviews via zoom and supported by documentation. The result of this research is PT. Cyber ​​Edu Inkor has been successful in promoting the cyber learning program well through the implementation of the 7P promotion mix and Business to Business (B2B) marketing so that cyber education in Indonesia is currently developing rapidly in line with the expectations of the establishment of the company. The method used is a qualitative research method, namely conducting virtual interviews via zoom and supported by documentation. The result of this research is PT. Cyber ​​Edu Inkor has been successful in promoting the cyber learning program well through the implementation of the 7P promotion mix and Business to Business (B2B) marketing so that cyber education in Indonesia is currently developing rapidly in line with the expectations of the establishment of the company. The method used is a qualitative research method, namely conducting virtual interviews via zoom and supported by documentation. The result of this research is PT. Cyber ​​Edu Inkor has been successful in promoting the cyber learning program well through the implementation of the 7P promotion mix and Business to Business (B2B) marketing so that cyber education in Indonesia is currently developing rapidly in line with the expectations of the establishment of the company.